The role of the physical education teacher in the education process based on selected Polish books published after 1989 - Beata Foszczyńska (University of Applied Sciences in Tarnow, Poland, 2018)
The subject of the article is the presentation of the role of physical education teacher in selected books published in Poland after 1989 year. Physical education teacher is played an important role in contemporary pedagogy. His tasks include not only the development of physical fitness of his students, but also the harmonious development of their personality, specially the moral and social sphere, in accordance with the principle of holistic pedagogy. The teacher should care for the right image of himself. He have to introduce the students into the world of the values of physical culture and be the guide to the values of sporting activity. The research used the bibliographic, analytical, descriptive and axiological methods and the technique of content analysis guided by the content and interpretation potential of the axiological dominant of books. The interpretation of axiological contents has shown the role of physical education teacher in the education process.